Social causes of non-passage in the training of children in modern times and their solution in the light of the Qur'an and Sunnah: Analytical study: عصرِ حاضر میں تربیت أطفال کی عدم پاسداری کےمعاشرتی أسباب اور قرآن و سنت کی روشنی میں ان کا حل:تجزیاتی مطالعہ - Abid ul Hassan, abidhasan; Ghulam Mustafa, ghumalmustafa (AL-IDRAK JOURNAL, 2021)
In fact, it is human nature to worship the rising sun. When Muslims dominated the world as a superior nation, they were proud of their values ​​and traditions. The system which Islam had ordained for them with the limits of seventy and hijab continued in the Muslim society with all its blessings and fruits. But in the twentieth century, when the English emerged on the page of history as conquerors, they changed the Muslim education system Which gripped the minds of generations of Muslims.In a society where a mother's embrace is considered the child's first school, an ideal mother is given priority over a thousand teachers. On the other hand, a teacher has been given the status of a spiritual father because of his ability to make the whole universe a school for the child. Unfortunately, due to the lack of trained teachers in today's society, the process of training children has also come to a standstill. Teachers' work is limited to salary increases and promotions۔ In addition, incidents of violence and beatings against children are also coming to light from many educational institutions۔ Violence against children by teachers is causing hatred in the hearts of children for teachers and deprivation of school.Adopting the method of the Prophet (peace and blessings of Allaah be upon him) in education and training can yield significant results. In the light of Islamic teachings, the training of children can be brought in the right direction.There is a need to train children on the principles of Islam so that they can emerge as active members of society.